Comparative Effects of Dexmedetomidine and Propofol on US-Guided Radiofrequency Ablation of Hepatic Neoplasm Under Monitored Anesthesia Care: A Randomized Controlled Study - Joung, Kyoung-Woon (Medicine (Baltimore), 2015)
Percutaneous radiofrequency ablation (RFA) is a useful and safe procedure for treating hepatic neoplasm. However, liver RFA causes severe pain, which thereby increases the demand for monitored anesthesia care (MAC). Here, we compared the efficacy and safety of propofol and dexmedetomidine, which are commonly administered during MAC when performing RFA to assess hepatic neoplasm. In this randomized controlled trial, 40 patients were randomly allocated to 2 groups for elective RFA. Patients received either dexmedetomidine (group D) or propofol (group P). Both groups received the continuous infusion of remifentanil for pain control. The primary outcomes were opioid consumption and differences in partial pressure of arterial carbon dioxide (PaCO(2)) between pre- and postprocedure RFA. In addition, hemodynamic parameters, patient satisfaction, and interventional radiologist satisfaction were determined. There were significant differences in opioid consumption (50.1 ± 16.8 ng/kg/min [group D] vs 71.2 ± 18.7 ng/kg/min [group P]; P = 0.001) and delta PaCO(2) (10.4 ± 6.4 mm Hg vs 17.2 ± 9.2 mm Hg, respectively; P = 0.016). Moreover, respiratory rates were significantly different between groups during RFA (P < 0.001). However, blood pressure and heart rate did not significantly change during RFA. Neither patient nor interventional radiologist satisfaction was significantly different between groups. Dexmedetomidine provides better respiratory stability and reduces opioid consumption in comparison with propofol when administered under MAC when performing RFA for hepatic neoplasm.